Presence of Oxytocin, Vasopressin and Atrial Natriuretic Peptide and Their Modification in Rat Hypothalamic Paraventricular Nucleus During Resistance Training. (3rd April 2013) - Farina, E. V.; Cappello, F.; Lipari, L.; Valentino, A.; Di Felice, V.; Valentino, B.
Summary Many studies have demonstrated the physiological effects of oxytocin (OT), atrial natriuretic peptide (ANP) and vasopressin (VP) in the homoeostasis of body fluids during physical exercise. However, a little information is available about the related immunohistochemical changes in hypothalamic magnocellular neurosecretory system during and after the training. The aim of the present work was to study the immunohistochemical changes in OT, ANP and VP levels in the hypothalamic paraventricular nucleus during and after resistance exercise protocol. Three groups of Wistar rats were trained by a rung ladder protocol for 15, 30 and 45 days, respectively; a fourth group was left to rest for 15 days after the training. Finally, four sedentary groups were used as controls. The results show that resistance training induces a significant reduction in the percentage of OT‐positive neurons, compared with sedentary controls. In contrast, this protocol did not induce any change in VP levels, and ANP levels did not change significantly. However, VP increased after the resting period of 15 days. Our work shows that neurons of the paraventricular nucleus are involved in body fluid homoeostasis during and after resistance exercise. The functional significance of these changes in OT and VP levels, during and after the protocol, needs to be further investigated.